Development of an Obesity Prevention Education Model Using Comic MediaDigital-Based Learning for Teenagers in Jambi City - Solihin Sayuti; Alpari Nopindra; Andriana Marwanto; Nur Ahmad Habibi (International Journal Of Health Science, 2025)
Obesity is a condition in which the body is overweight, as measured by several measurements. The accumulation of fat in the body's subcutaneous tissue, or under the skin, around organs, and sometimes even in the tissue itself, is a sign of obesity. In the past five years, the prevalence of adolescent obesity in Indonesia has nearly doubled. Objective:The production of digital comics on obesity prevention for teenagers.Method:This study used an RnD approach based on the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. The media was validated by media expert validators, linguists, public health practitioners, agency validators, and students of SMKN 4 Jambi City. Data collection used a literature review, and data were analyzed manually.Results:The development of a digital comic for obesity prevention at SMKN 4 Jambi City began with identifying potential and problems, collecting data, and information. The product design was created using the Canva application. The product received validation results, namely 95% from media experts (very suitable), 93% from language experts (very suitable), 98% from public health practitioners (very suitable), and 100% from institutions consisting of teachers (very suitable). After receiving suggestions and comments from the validators, the product was then revised. Then the results of the product trial on the participant group were 88% (very suitable).Conclusion:Digital comics on obesity prevention can be used as a health education medium with a very good feasibility test. Recommendation: Digital comics on obesity prevention can be digitized on an Android basis